Decompressive Hemicraniectomy in Hypertensive Basal Ganglia Hemorrhages (Pulse, 2016)
Objectives: The aim of this study was to analyze efficacy and safety of decompressive hemicraniectomy (DHC) in hypertensive basal ganglia hemorrhage (HBGH). Neurosurgical management of HBGH is still a controversial issue. Surgical techniques are diverse, from the open large craniotomy, to the minimally invasive techniques like stereotactic aspiration of the HBGH, endoscopic evacuation and stereotactic catheter drainage after instillation of thrombolytic agents. Decompressive hemicraniectomy lowers intracranial pressure and improves outcome in patients with HBGH.Methods: 8 patients with HBGH who underwent decompressive craniectomy in the last 2 years were analyzed. Parameters investigated included clinical presentations, radiologic profile, time interval from ictus to surgery, and modified Rankin Scale score at 6 months.Results: The patients mean age 55 years, the mean Glasgow Coma Scale (GCS) score was 7 (range 513), the mean ICH volume was 58 ml (range 4070 ml), and the mean midline shift was 10.62 mm (range 6-16 mm). The outcome after 6 months was appreciated as good (modified Rankin Scale 04) or poor (modified Rankin Scale 5-6). Five patients had good and three had poor outcomes (including two deaths).Conclusion: We conclude, based on this small cohort, that DC can reduce mortality in some cases. Larger prospective studies are needed to assess safety and efficacy of this method.Pulse Vol.8 January-December 2015 p.38-42